Global inventory of Wetlands and their role in the carbon cycle - Sudip Mitra; Reiner Wassmann; Paul L. G. Vlek (University of Bonn, Center for Development Research (ZEF), 2003)
Wetlands are among the most important natural resources on earth, as sources of biological, cultural and economic diversity. Conservation and management of wetlands have been identified as priority tasks for action in international conventions and regional policies, but extensive wetland area has been degraded in many developing countries. These continuing destruction demands to be restricted or at least slowed down. The primary objectives of this study were (i) assessing ecological functions and concepts for sustainable use of wetlands and (ii) compiling relevant information sources on geographic distribution of wetlands as well as their role in the global carbon budget. Wetlands comprise a pivotal global carbon reservoir and can moreover sequester additional carbon from the atmosphere in form of soil organic matter. Pristine wetland soils are a source of the greenhouse gas methane, but- under improper management - these soils emit even larger quantities of the greenhouse gas carbon dioxide. The discussion on wetland protection measures is thwarted by uncertainties in the estimated carbon pool sizes and flux rates. On the global scale, the estimates on the carbon pool size vary from 200 to 530 Gt C while our own assessment (by incorporating global soil maps) clearly points towards the lower end of this range. Likewise, estimates of the carbon sequestration potential of wetlands vary between 80 to 230 Tg C/ yr. These discrepancies may in part be due to inherent problems in global land cover surveys, but diverging definitions of the ecosystem 'wetlands' (especially in dealing with peatlands) are further confounding an appraisal of global wetland resources. Similar uncertainties as for the global estimates arise for the geographic distribution of wetlands as described in different data sources. The three published world maps on wetland resources only coincide in 20-30 % of the identified wetland area. Our compilation of data on quantity and distribution of the wetland carbon pool allows an identification of potential hot spots' of future emissions and could feed into development of research and conservation projects. There are many reasons in favor of protection or a 'wise use' of wetlands that maintains the basic features of the ecosystem. The significance of wetlands for the global carbon budget and thus, for climate change, is a crucial pro-conservation argument that has been substantiated in this study through findings from current research.
Keywords: 330; Environmental Economics and Policy; Land Economics/Use; Feuchtgebiet; Umwelt; Treibhausgas-Emissionen; Klimaschutz; Räumliche Verteilung; Naturschutz; Welt; Entwicklungsländer